2013
DOI: 10.1002/pbc.24605
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of cixutumumab in children, adolescents, and young adults with refractory solid tumors: A report from the Children's Oncology Group

Abstract: Purpose This phase 2 study was designed to assess the efficacy of single agent cixutumumab (IMC-A12) and gain further information about associated toxicities and pharmacodynamics in children, adolescents, and young adults with recurrent or refractory solid tumors. Patients and Methods Patients with relapsed or refractory solid tumors were treated with 9 mg/kg of cixutumumab as a 1-hour IV infusion once weekly. Strata included: osteosarcoma, Ewing sarcoma, rhabdomyosarcoma, neuroblastoma (evaluable disease), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 29 publications
0
93
0
2
Order By: Relevance
“…Monotherapy trials of anti-IGF-1R antibodies and TKIs have generally reported disease stabilisation and minor responses, with few objective responses in common cancers [34–38]. There is, however, evidence of activity in heavily pre-treated Ewing sarcoma (EWS), other types of sarcomas, and neuroendocrine tumors, although data in the latter are conflicting [32,3944]. In addition, IGF-1R antibodies were recently reported to have single agent activity in recurrent ovarian cancer and relapsed thymoma, although thymoma treatment was associated with the development of autoimmune conditions including red cell aplasia [45,46].…”
Section: Clinical Trials: Reality Checkmentioning
confidence: 99%
“…Monotherapy trials of anti-IGF-1R antibodies and TKIs have generally reported disease stabilisation and minor responses, with few objective responses in common cancers [34–38]. There is, however, evidence of activity in heavily pre-treated Ewing sarcoma (EWS), other types of sarcomas, and neuroendocrine tumors, although data in the latter are conflicting [32,3944]. In addition, IGF-1R antibodies were recently reported to have single agent activity in recurrent ovarian cancer and relapsed thymoma, although thymoma treatment was associated with the development of autoimmune conditions including red cell aplasia [45,46].…”
Section: Clinical Trials: Reality Checkmentioning
confidence: 99%
“…Notably, 10 patients with ACC were treated with cixutumumab alone in a phase II study and no objective responses were reported. One patient achieved SD for 7 cycles 83 . In addition, a small-molecule TKI of the IGF-IR (OSI-906) is being investigated.…”
Section: Evidence Synthesismentioning
confidence: 97%
“…Unfortunately, the preclinical anti-RMS activity of targeted agents such as mTOR inhibitors (Hosoi et al 1999) and neutralizing IGF1 receptor antibodies (Mayeenuddin et al 2010) have not translated thus far into durable objective response rates in early-phase clinical trials (Geoerger et al 2012;Pappo et al 2014;Weigel et al 2014). However, improved event-free survival of individuals with relapsed RMS after treatment with the mTOR inhibitor temsirolimus in combination with vinorelbine and cyclophosphamide supports experimental strategies involving combinations of targeted agents and established drugs (Mascarenhas et al 2014).…”
Section: Box 1 the Banbury Center At Cold Spring Harbor Laboratorymentioning
confidence: 99%